Tomorrow's learning: involving everyone : learning with and about technologies and computing : 11th IFIP TC 3 World Conference on Computers in Education, WCCE 2017, Dublin, Ireland, July 3-6, 2017, Revised selected papers /: learning with and about technologies and computing : 11th IFIP TC 3 World Conference on Computers in Education, WCCE 2017, Dublin, Ireland, July 3-6, 2017, Revised selected papers. (2017) - Unknown
No abstract available